2005
DOI: 10.1126/science.1114867
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Surface Temperature Trends and Variability in the Tropical Atmosphere

Abstract: 26. We chose these values of the target factors to produce our final results because we have concluded that they are the most likely to be free of errors. They are calculated from oceanic observations to reduce errors from uncorrected diurnal variations, and we use unweighted MSU channel 2 data (T2 in SOM) to avoid additional noise due to the differencing procedure used to calculate TLT. The values of the intersatellite offsets needed to be recalculated to remove obvious intersatellite differences. In the supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
274
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(318 citation statements)
references
References 25 publications
38
274
3
3
Order By: Relevance
“…For comparison the radiosonde datasets have been vertically averaged with weightings to create equivalent MSU retrieved bulk temperatures for T4 (stratosphere), T2 (troposphere), and T2LT (lower troposphere). For reference we also show the trend from the Hadley Centre Climatic Research Unit, version 3 (HadCRUT3), surface records (Brohan et al 2006), and theoretical expectation from an ensemble of climate models (Santer et al 2005). Figure 9 shows the spread of trend estimates from this ensemble of homogenizations for the tropical satellite era.…”
Section: Spanning the Range And Comparison To Other Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison the radiosonde datasets have been vertically averaged with weightings to create equivalent MSU retrieved bulk temperatures for T4 (stratosphere), T2 (troposphere), and T2LT (lower troposphere). For reference we also show the trend from the Hadley Centre Climatic Research Unit, version 3 (HadCRUT3), surface records (Brohan et al 2006), and theoretical expectation from an ensemble of climate models (Santer et al 2005). Figure 9 shows the spread of trend estimates from this ensemble of homogenizations for the tropical satellite era.…”
Section: Spanning the Range And Comparison To Other Datasetsmentioning
confidence: 99%
“…However, when considering the more recent satellite era (1979 onward), the same radiosonde datasets indicate that the troposphere is warming at a slower rate than at the surface, particularly within the tropics. This is at odds with climate models, which predict amplification of the surface trends in the tropics (Santer et al 2005;Karl et al 2006). Some Microwave Sounding Unit (MSU) satellite records indicate similar changes in the troposphere to radiosonde records (Christy and Norris 2006), whereas others are in broad agreement with the model predictions (Mears and Wentz 2005;Vinnikov et al 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Led by Santer, a large team including many highprofile climate scientists, then showed that the new data set was in good agreement with computer models 4 .…”
Section: Class Of 1998: Benjamin Santermentioning
confidence: 96%
“…Ряды на основе радиозондо-вых данных демонстрируют существенное понижение температуры тропосферы в период до середины 1970-х годов. Это понижение лишь начи-ная со второй половины 1970-х годов после хорошо известного из литературы скачкообразного повышения температуры тропосферы, связываемого с пере-стройкой циркуляционных режимов Северного полушария (Santer et al, 2005), сменилось последовательным потеплением. …”
Section: временные ряды аномалий температуры в тропосфере за период пunclassified
“…На изменения и колебания температуры в тропосфере влияние оказы-вают как вызванные человеческой деятельностью процессы выброса парниковых газов, так и процессы в системе «океан-атмосфера» временного масштаба нескольких лет, в частности, положительные и отрицательные фазы явления Эль-Ниньо. Влияние же особенностей рельефа, свойств подсти-лающей поверхности на температуру в тропосфере менее значительно, чем на приземную температуру, поэтому рядом авторов (Santer et al, 2005) выска-заны предположения о «меньшей зашумленности» сигнала температуры в тропосфере по сравнению с сигналом приземной температуры.…”
Section: Introductionunclassified